Construction of Public Opinion on Environmental Issues in the Media - Juraitė, Kristina (Sociologija. Mintis ir veiksmas, 2002)
After more than a decade of political independence it is interesting to study relationship between relatively free mass media and people’s thinking and saying about the environment in the postcommunist society. In the following sections, social constructionist perspective is analyzed, research methods applied in the study are presented, and the results of public environmental perceptions and the data of environmental coverage in the main dailies in Lithuania are examined. At the end, the discussion of theoretical assumptions and empirical results follows.